Psychosocial Effects in Educational Organizations in the City of Quito, Ecuador - Flores Batallas, Efraín (2016)
Organizations usually offer the possibility of managing the human factor from the business platform, impart knowledge and share experiences in the classroom. They are aware of the importance of assessing their psychosocial aspects and seek to prevent possible psychological disorders that affect their health and, therefore, their performance. This approach has as its main focus the happiness of the human factor at work. The work performed by employees is decisive in the achievement of business goals and, of course, for personal development; however, we shouldn’t forget that there are factors that compromise the worker’s health and well-being. There is, for example, the presence of psychosocial elements that influence the disposition at work, such as double presence, role conflict, motivation, development possibilities, and so on. On this basis it is desired to put to the reader’s consideration the psychological harassment at work (mobbing) as a peculiarity of psychosocial evaluation.